Evaluation of the intensive care management of patients with spinal cord trauma - Mehmet Akif Durak; Mustafa Said Aydogan; Muhammet Gokhan Turtay (Medicine Science, 2018)
Spine traumas and the resulting spinal cord injuries are among the most important health problems with their physical and psychosocial impacts due to significant mortality and morbidity. Our objective in this study was to evaluate the issues that should be taken into consideration during the intensive care treatment management of patients monitored for spinal cord trauma. Patient files were examined for obtaining the demographic and clinical properties of 68 patients followed up with spine trauma diagnosis at the Intensive Care Unit during the dates of June 2011- 2016. Age, gender, cause of trauma, trauma localization, trauma injury accompanying the spine trauma, deep vein thrombosis development, infection development, ASIA (American Spinal Injury Association) score, duration of intensive care stays, and properties were examined. An evaluation was made in our study according to ASIA scoring as a result of which it was determined that there are 4 ASIA A patients (5.88%) hospitalized or discharged, 5 ASIA B patients (7.35%), 14 ASIA C patients (20.58%), 24 ASIA D patients (35.29%) and 5 ASIA score E (neurologically intact) (7.35%) patients, while mortality rate was determined as 16 patients (23.52%). It was determined as a result of the evaluation carried out with regard to post-trauma intensive care unit length of stays that the average length of stay was 21.3 days with the shortest length of stay as 1 day and the longest as 96 days. Care attributes should be familiar for this patient group that requires a multidisciplinary approach and serious rehabilitation and a sufficient level of knowledge should be reached by all those involved in the follow-up procedure. [Med-Science 2018; 7(3.000): 561-4]